Triple negative breast cancer: the kiss of death - Jitariu, Adriana-Andreea; Cîmpean, Anca Maria; Ribatti, Domenico; Raica, Marius (Oncotarget, 2017)
One of the most controversial women malignancies, triple negative breast cancers (TNBCs) are critically overviewed here, being focused on data useful in clinical practice or to improve the therapy and patients survival. TNBCs "choose" young women and its "kiss" is, unfortunately deadly in most cases. Currently, few sparse data are available in literature concerning the origins of TNBC. Vasculogenic mimicry detected in TNBCs, seems to be determined by a population of CD133+ cells and may be stimulated by different pharmacological agents such sunitinib. Despite the fact that TNBCs do not usually metastasize through the lymphatic pathways, TNBCs may be characterized by lymphatic invasion and by an increased lymphatic microvascular density. If TNBCs treatment depends on the molecular profile of the tumor, the same statement may be postulated for TNBCs metastasis. Whether metastases have a similar phenotype as the primary tumor remains an enigma. Therefore, the question: 'Could TNBC be subject to a standardized, unanimously accepted therapeutic strategy or is it strictly subclass-dependent?' remains to be further investigated.